Just Between Us - Carrol, Jacqueline (London HarperCollinsEntertainment, 2002)
Mary-Kate & Ashley star as twins Chloe and Riley Carlson in this hilarious new series, based on the hit TV show, SO LITTLE TIME
Include Illustration
Keywords: Carlson, Chloe (Fictitious character) -- Juvenile fiction -- Carlson, Riley (Fictitious character) -- Juvenile fiction -- Sisters -- Juvenile fiction